Design, Analysis and Stability testing of Lunar Lander for Soft-Landing. (2020) - Aravind, G.; Vishnu, S.; Amarnath, K.V.; Hithesh, U.; Harikrishnan, P.; Sreedharan, Pramod; Udupa, Ganesh
Abstract: The part that first comes in contact with the ground is the base of the lander-footpad. The response to impact of the footpad is very important. The footpad should be able to withstand the impact forces a reasonable number of times, for various landing experiments. It should be both lightweight and strong and at the same time it should be able to absorb a large amount of shock and transmit only a smaller portion towards the legs. A scaled down model was chosen and the footpad was designed and fabricated for that model. The model was designed, simulated and analyzed for its durability. The shock absorbers on the legs also play an important role for maintaining the stability of the lander. Experiments were conducted for the static and dynamic stability of the lunar lander for soft landing and found out the angle at which the lander topples.